Analisis Pengendalian Internal Berbasis COSO pada Pengelolaan Keuangan Gereja Protestan Maluku - Patty, Meidylisa (Journal of Applied Accounting, 2026)
This study aims to analyze the implementation of Internal Control Systems (ICS) in the financial management of the Protestant Church of Maluku (GPM) based on the Committee of Sponsoring Organizations of the Treadway Commission (COSO) framework and to position it within the perspective of Accounting Information Systems (AIS). A qualitative approach with an embedded case study design was employed at the Classis and Congregation levels in Ambon. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that although GPM structurally possesses formal internal control mechanisms, their effectiveness remains limited. The control environment is dominated by trust-based governance and leadership centralization; risk assessment is not systematically documented; control activities are constrained by inadequate segregation of duties and the use of a cash-based single-entry system; and financial reporting relying solely on budget realization reports limits risk-based monitoring. The study recommends transitioning to accrual-based and double-entry accounting systems, strengthening standard operating procedures, and implementing integrated digital monitoring to enhance accountability and organizational sustainability. Keywords: COSO, internal control system, accounting information system, faith-based organization, accountability.